Dynamics of Water Absorption in Callovo-Oxfordian Claystone Revealed With Multimodal X-Ray and Neutron Tomography - Stavropoulou, Eleni; Andò, Edward; Roubin, Emmanuel; Lenoir, Nicolas; Tengattini, Alessandro; Briffaut, Matthieu; Bésuelle, Pierre (Frontiers in Earth Science, 2020)
The Callovo-Oxfordian claystone is a material with notoriously complex hydro-mechanical behaviour. Combined neutron and x-ray tomography modalities are used for the first time to characterise the dynamics of water absorption in this material by comparing material deformation as well as water arrival. Exploiting recent work on multimodal registration, neutron and x-ray datasets are registered pairwise into a common coordinate system, meaning that a vector-valued field (i.e. neutron and x-ray reconstructed values) is available for each timestep, essentially making this a 5D dataset. The ability to cross-plot each field into a joint histogram (an inherent input into the registration) allows an improved identification of mineral phases in this complex material. Material deformation obtained from the application of Digital Volume Correlation on the x-ray timeseries data is locally compared to changes in water content available from the neutrons, opening the way towards a quantitative description of the hydro-mechanics of this process.